Interpersonal skills in organizations - De Janasz, Suzanne C; Dowd, Karen O.; Schneider, Beth Z. (McGraw-Hill/Irwin, 2012)
The book is organized into 4 distinct sections (Understanding Yourself, Understanding Others, Understanding Teams, and Leading) that can be used collectively or modularly depending on the instructors' preferences and students' needs.